2021
DOI: 10.1111/1742-6723.13914
|View full text |Cite
|
Sign up to set email alerts
|

Profile and outcomes of emergency department presentations based on mode of arrival: A state‐wide retrospective cohort study

Abstract: Objective Understanding how people arrive to the ED assists in planning health services' response to fluctuating ED demand. The present study aimed to describe and compare demographics, clinical characteristics and health service outcomes of adult ED patient presentations based on mode of arrival: brought in by police (BIBP)/brought in by ambulance (BIBA)/privately arranged transport (PAT). Methods A retrospective cohort study of ED patient presentations made between 1 January 2018 and 31 December 2020 from al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…They were significantly different than their non‐EMS counterparts, both in baseline patient characteristics (eg, older and sicker) and in site‐of‐care management. Our finding mirrors the reality that the overall EMS population is more commonly hospitalized than those arriving at the ED by other means 10,29,30 . The 2018 National Hospital Ambulatory Care Survey found 3‐fold higher hospitalization for patients arriving by EMS (30.2% vs 9.9%) 15 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…They were significantly different than their non‐EMS counterparts, both in baseline patient characteristics (eg, older and sicker) and in site‐of‐care management. Our finding mirrors the reality that the overall EMS population is more commonly hospitalized than those arriving at the ED by other means 10,29,30 . The 2018 National Hospital Ambulatory Care Survey found 3‐fold higher hospitalization for patients arriving by EMS (30.2% vs 9.9%) 15 .…”
Section: Discussionsupporting
confidence: 77%
“…Our finding mirrors the reality that the overall EMS population is more commonly hospitalized than those arriving at the ED by other means. 10,29,30 The 2018 National Hospital Ambulatory Care Survey found 3-fold higher hospitalization for patients arriving by EMS (30.2% vs 9.9%). 15 This survey was broad, and its analysis was limited to age, sex, race, ethnicity, and insurance type.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified several factors predictive of an ED LOS ≥4 hours and hospital admission for patient presentations BIBP. This finding adds to previous literature that has highlighted the existence of clinical and demographic differences between people BIBP and not BIBP [9,10], but not necessarily the strength of the difference. These and 8 other findings [8] support the need to further understand and develop specialised care pathways for people BIBP.…”
Section: Discussionsupporting
confidence: 69%
“…With a high prevalence of mental and complex physical conditions among people BIBP to the ED evident in single site studies, a broader understanding of patient and care delivery factors that impact this vulnerable cohort is needed. This state-wide study extends an earlier single-site study that examined the characteristics and health service outcomes of adult ED patient presentations based on mode of arrival (police/ambulance/privately-arranged transport) [10]. The aim of this current study was to identify factors that predict an ED LOS ≥4 hours and hospital admission in order to contribute to evidence-based informed approaches for this mode of arrival.…”
Section: Introductionmentioning
confidence: 72%
“…People can be BIBP to the ED from several locations including short‐term custodial settings (i.e., watch‐houses, custody suites and jails), prisons or the community (Crilly et al., 2019). Compared to people arriving to the ED by other means, people BIBP are more likely to present for mental and behavioural issues, substance misuse and encounter a longer ED length of stay (Brownlea et al., 2019; Crilly et al., 2019; Wardrop et al., 2022b). In a recent scoping review that examined people BIBP to the ED and included 21 studies from several countries, the main presentation type was mental health/psychiatric reasons followed by trauma/injury and substance misuse (Wardrop et al., 2023).…”
Section: Introductionmentioning
confidence: 99%